POTENSI RIZOBAKTERI INDIGENUS SEBAGAI AGENS BIOKONTROL JAMUR FUSARIUM OXYSPORUM F. SP. CUBENSE PENYEBAB PENYAKIT LAYU TANAMAN PISANG - Selviana Anggraini; Jumsu Trisno; Tizelia Tizelia (LPPM Universitas Bina Insan, 2020)
The use of rhizobacteria is an alternative control in suppressing plant disease attacks. The purpose of this study was to obtain indigenous rhizobacteria which have the potential as antagonist agents of Fusarium oxysporum f. sp. cubense. Sampling was carried out randomly selected on endemic lands. Isolation of rhizobacteria using serial dilution method and its antagonist test against Fusarium oxysporum f. sp. cubense uses the dual culture method. The isolation results from 3 banana cultivars (kepok, raja sere, and mas) obtained 24 rhizobacterial isolates with different morphological and physiological characters. The antagonist test results showed that 8 rhizobacterial isolates were able to suppress the growth of Fusarium oxysporum f. sp. cubense and is not plant pathogenic.